SARS-CoV-2 computer simulation of sterilization via electrical resistance in air conditioning - Jorge Henrique de Oliveira Sales; Diego Ramos do Nascimento; Cláudio Soriano de Souza Brandão; Rodrigo Gaigher Cezana; Francisco Bruno Souza Oliveira (The Journal of Engineering and Exact Sciences)
In search of reinvention in the middle of the pandemic, an equipment adapted from a system that controls morph for indoor environments that have air conditioners is proposed.  This paper presents a study via computational modeling to test the effect of electrical resistance as an air filter against SARS-CoV-2. The mode of transmission of SARS-CoV-2 includes, for example, transmission via contact, droplets, and aerosols present in indoor humidity. Therefore, aerosol spread of SARS-CoV-2 is similar to the indoor spread of the morph. The result shows that the system works by eliminating the humidity in the air containing SARS-CoV-2. What we are trying to demonstrate is that an electrically resistive filter controls the spread of the virus in air up to 10 cubic meters in size indoors. This system does not replace existing filters, but is a piece of equipment to help control SARS-CoV-2.